Detailed Kinetic Modeling of Lignin Pyrolysis for Process Optimization - Hough, Blake R; Schwartz, Daniel T; Pfaendtner, Jim (Industrial & engineering chemistry research, 2016)
Biomass valorization through thermochemical conversion of lignocellulosic feedstocks is limited by our lack of detailed kinetic models. In addition to adding mechanistic understanding, more detailed models are needed to optimize industrial biomass pyrolysis processes for producing fuels and chemicals. To this end, a kinetic model for lignin pyrolysis involving ∼100 species and 400 reactions is presented which is capable of predicting the temporal evolution of molecules and functional groups during lignin pyrolysis. The model provides information beyond the lumped yields of common pyrolysis models without any fitting, allowing it to cover a wider range of feedstocks and reaction conditions. Good agreement is observed with slow pyrolysis experiments, and an exhaustive global sensitivity analysis using over 2 million simulations sheds light on reactions that contribute most to the variance in model predictions. Model predictions for fast pyrolysis are available, but data from kinetically controlled experiments has yet to be generated for lignin fast pyrolysis.